Recombinant Annexin A2 Administration Improves Neurological Outcomes After Traumatic Brain Injury in Mice - Cheng, Chongjie; Wang, Xiaoshu; Jiang, Yinghua; Li, Yadan; Liao, Zhengbu; Li, Wenlu; Yu, Zhanyang; Whalen, Michael J.; Lok, Josephine; Dumont, Aaron S.; Liu, Ning; Wang, Xiaoying (Frontiers in Pharmacology, 2021)
Microvascular failure is one of the key pathogenic factors in the dynamic pathological evolution after traumatic brain injury (TBI). Our laboratory and others previously reported that Annexin A2 functions in blood-brain barrier (BBB) development and cerebral angiogenesis, and recombinant human Annexin A2 (rA2) protected against hypoxia plus IL-1β-induced cerebral trans-endothelial permeability in vitro, and cerebral angiogenesis impairment of AXNA2 knock-out mice in vivo. We thereby hypothesized that ANXA2 might be a cerebrovascular therapy candidate that targets early BBB integrity disruption, and subacute/delayed cerebrovascular remodeling after TBI, ultimately improve neurological outcomes. In a controlled cortex impact (CCI) mice model, we found rA2 treatment (1 mg/kg) significantly reduced early BBB disruption at 24 h after TBI; and rA2 daily treatment for 7 days augmented TBI-induced mRNA levels of pro-angiogenic and endothelial-derived trophic factors in cerebral microvessels. In cultured human brain microvascular endothelial cells (HBMEC), through MAPKs array, we identified that rA2 significantly activated Akt, ERK, and CREB, and the activated CREB might be responsible for the rA2-induced VEGF and BDNF expression. Moreover, rA2 administration significantly increased cerebral angiogenesis examined at 14 days and vessel density at 28 days after TBI in mice. Consistently, our results validated that rA2 significantly induced angiogenesis in vitro, evidenced by tube formation and scratched migration assays in HBMEC. Lastly, we demonstrated that rA2 improved long-term sensorimotor and cognitive function, and reduced brain tissue loss at 28 days after TBI. Our findings suggest that rA2 might be a novel vascular targeting approach for treating TBI.